O5-S1.05 Computer assisted self interviewing in a sexual health clinic as part of routine clinical care: impact on service and patient and clinician views. (10th July 2011) - Vodstrcil, L; Hocking, J; Cummings, R; Chen, M; Bradshaw, C; Read, T; Sze, J; Fairley, C
Abstract : Background: Computer assisted self interviewing (CASI) has been used at the Melbourne Sexual Health Centre (MSHC) in Victoria, Australia since June 2008, to obtain a pre-consultation sexual risk history. We aimed to evaluate the impact of CASI on consultation times, STI testing rates, patient response rates to CASI questions, and obtain patient and clinician views on CASI. Methods: The proportion of patients who declined to answer questions using CASI since 2008 was calculated. We then used the same 12 week period (Feb to May) over three years (2008 pre-CASI), (2009 CASI period), and (2010 non-CASI period-due to a computer theft) to assess consultation times and STI-testing rates. We carried out surveys of clinicians and patients to determine their experience and the acceptability of CASI as part of routine clinical practice. Results: 14 190 patients completed CASI during the audit period. Men were more likely than women to decline questions about the number of partners they had of the opposite sex (4.4% v 3.6%, p=0.05) and same sex (8.9% v 0%, p<0.01). One third (34%) of HIV-positive men did not answer questions on number of partners and 18% declined questions about condom use with insertive anal sex. There was no difference in the mean consultation times during CASI and non-CASI operating periods (p?0.17). Only the proportion of women tested for chlamydia differed between CASI and non-CASI periods (p<0.01, 84% v 88% respectively). 267 patients completed the survey about CASI. Most (72% men and 69% women) were comfortable using the computer and reported that all their answers were accurate (76% men and 71% women). Half preferred CASI but 18% would have preferred a clinician to have asked the questions. 39 clinicians completed the staff survey, but a varying proportion (11%–44%) felt that face-to-face interviewing was more accurate, depending on the risk factor. Only 5% were unsatisfied with CASI. Conclusions: This is the first evaluation of CASI operating routinely in a sexual health clinic. We have demonstrated that CASI is acceptable to most patients and clinicians in a sexual health setting and does not adversely affect various measures of clinical output. The true value of CASI is most likely to be realised when it is integrated with further innovations in clinical care such as the development of express clinical services, decision support software and detailed behavioural surveillance system.